Teaching Mathematics as to be Meaningful - Foregrounding Play and Children's Perspectives Results from the POEM5 Conference, 2022 - Palmér, Hanna; Björklund, Camilla; Reikerås, Elin; Elofsson, Jessica (Springer Nature, 2024)
This open access book's theme is Teaching mathematics as to be meaningful - foregrounding children's play and perspectives. It discusses the relation between teachers, children and mathematical content within the context of play with a particular focus on the framing of these relations within this context, which is an important theme in the debate on whether teaching should be integrated with or separated from children's play. The work further addresses meaningfulness in the learning process, particularly from the child's perspective. Globally, most guidelines and curricula for early childhood education mention play as one of the key features for young children's learning. Still, there are quite different views on the definitions of play and in what ways play should become part of children's learning. The chapters of the book mirror the research topics presented at the fifth POEM conference in May 2022 divided into four sub-themes: Play and learning, Children's perspectives on mathematics, Teachers' competencies and Theorizing aspects of early mathematics education.